The ghostway eaudiobook - Hillerman, Tony (Leaphorn and Chee, 2018)
An old man's hazy memory and a Polaroid snapshot are all Chee has to go on, but they are enough to send him deep into an underworld of murder and revenge when a shootout erupts between two strangers at the Shiprock Wash-O-Mat. One man dies and the other drives off, but not before showing old Joseph Joe a photograph of the man he is looking for. It's not much of a lead for Sergeant Chee, but it's enough to put him on the killer's trail.